Strategi Pengembangan Kawasan Wisata Gunung Nona Kecamatan Anggeraja Kabupaten Enrekang, Indonesia - Jasman, Jasman; Ridwan, Masri (LaGeografia, 2020)
The aim study was to identify the development strategy of the Mount Nona area of Tanete Village, Anggeraja District, Enrekang Regency, South Sulawesi, Indonesia. Although it is located in a strategic location that connects Makassar and the Toraja Destinations, this region faces several challenges, so efforts are needed to uncover the development of a sustainable tourism industry. The approach used is qualitative descriptive. Data collection by field survey and Focus Group Discussion (FGD) with stakeholders. The results showed that the Mount Nona Region was in quadrant I, which is a rapid growth strategy. Quality improvement is important, optimizing land use and developing innovative and up-to-date promotional brands. The strategy used to achieve this is with Ecotourism and the preparation of tour packages. It is expected that the findings of this study will be followed up by stakeholders in order to optimize the tourism industry in the Mount Nona tourism area.